Performance Test of Double Crossed Membrane Contactor for Simultaneous Absorption-Desorption Of CO2 Using Diethanolamine - Rahmawati, Yeni; Iswanto, Toto; Rifa’i, Muhammad (IPTEK Journal of Proceedings Series, 2015)
This study aimed to test the performance of polypropylene hollow fiber that were configured in the double crosses configuration as membrane contactor by combining absorption-desorption process simultaneously in one module using diethanolamine as solvent which is expected to separate CO2 optimally by using of minimal solvents. The solvent allowed to stand in the shell module, feed gas supplied to the lumen of the first tube, and sweep gas flowed into the lumen of the second tube of membrane module. The experimental results showed that during the first three hours, the flux of absorption decreased until 2.63x10-5 mol/m2.s and the efficiency of absorption decreased to 5.181%, whereas flux of desorption increased every hour until 6.202x10-5 mol/m2.s during performance test, while the efficiency of desorption rose to 92.437%.